Theoretical considerations that sustain the system of educational actions to strengthen the identity of sports culture in children in the practice of football of the Bayamo municipality (Review) (Revista científica Olimpia, 2018)
The investigation is based in designing a system of educational actions as from sports recreational offers to strengthen the identity of the sports culture like fundamental value in children of 10 and 12 years in the practice of the Soccer at Bayamo's municipality, since through decades a sentiment for this sports, because it has to a large extent been  contributed to seeing the life from a different mode in the population, once him was  bound one way or another has been  rooted, either to practice it or to follow it like fan.
Keywords: educational actions; value; identity; sports